Objectively measured near work, outdoor exposure and myopia in children - Wen, Longbo; Cao, Yingpin; Cheng, Qian; Li, Xiaoning; Pan, Lun; Li, Lei; Zhu, HaoGang; Lan, Weizhong; Yang, Zhikuan (British journal of ophthalmology, 2020)
AimTo reassess the association between near work, outdoor exposure and myopia in children through an objective approach.MethodsEighty-six children (10.13±0.48 years) were asked to wear Clouclip, a newly developed wearable device that is able to measure working distance and eye-level illuminance, for a complete week to obtain information on near work and outdoor exposure. The mean daily Clouclip wearing time was 11.72±1.14 hour. The spherical equivalent refraction was determined by cycloplegic autorefraction.ResultsThe myopic children were found to be exposed to light intensities >3000 lux (0.68±0.50 hour vs 1.02±0.53 hour, p=0.012) and >5000 lux (0.42±0.35 hour vs 0.63±0.31 hour, p=0.004) for shorter durations on average each day than the non-myopic children. Additionally, the myopic children spent more time on average each day on activities at a distance of <20 cm than non-myopic children (1.89±0.61 hour vs 1.52±0.77 hour, p=0.019). In the multivariate logistic analysis, the time spent with a higher light intensity (>3000 lux (OR=0.27, 95% CI: 0.10 to 0.72, p=0.009); >5000 lux (OR=0.11, 95% CI: 0.02 to 0.56, p=0.008)) and a working distance of <20 cm (in a circumstance of >3000 lux (OR=1.17, 95% CI: 1.09 to 1.86, p=0.038) or in that of >5000 lux (OR=1.12, 95% CI: 1.03 to 1.77, p=0.046)) were the independent protective factors and risk factors, respectively.ConclusionThe current study provides novel evidence, based on objective data, to support the association between the intensity of near work, light intensity and myopia. However, the causality and the dose-effect relationship need to be investigated further.